1931
DOI: 10.11606/issn.2318-8227.v27i0p112-134
|View full text |Cite
|
Sign up to set email alerts
|

Finanças do Brasil

Abstract: Finanças do Brasil i A SITUAÇÃO ATUAL Ouve-se que o Brasil é paiz perdido. Deve acima das suas possibilidades econômicas. Não tem ordem nos orçamentos, como não na tem nas leis, na politica e na administração. Tudo lhe corre á matroca. Já não se contam as acusações aos seus homens públicos; uns como delapidadores das rendas do Estado; outros, nas mais altas posições, por mentirem, até em comunicados oficiais, ás cortes estrangeiras. Aqui, o peculato; ali, a rebeldia armada; e, para todos, por sistema, a graça … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In addition, practical and cultural factors lead to a strong appreciation of traditional/homemade meals. As a result, Brazilians primarily consume unprocessed or minimally processed foods and culinary preparations made from these ingredients [30,31]. Our study found that the children mainly consumed foods that are part of the traditional Brazilian diet, such as rice, beans, meat, fruits, and vegetables.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, practical and cultural factors lead to a strong appreciation of traditional/homemade meals. As a result, Brazilians primarily consume unprocessed or minimally processed foods and culinary preparations made from these ingredients [30,31]. Our study found that the children mainly consumed foods that are part of the traditional Brazilian diet, such as rice, beans, meat, fruits, and vegetables.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, a significant proportion of the population cannot afford to eat out and must instead cook at home. Positive income elasticity suggests that families with higher incomes are more likely to eat out [30,39]. Future studies should consider the correlation between cost and time.…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos anos, a filosofia de educação tem se debruçado sobre os temas da alteridade/outredade 4 e da liberdade 5 na perspectiva de Paulo Freire (1921Freire ( -1997 como forma de enfrentar a polarização político-social que caracteriza as relações sociais no contexto em que vivemos. Os discursos hegemônicos e autoritários do governo Bolsonaro e sua rede de apoiadores, ainda mesmo durante a campanha eleitoral de 2018, a serviço do sistema capitalista neoliberal, têm adotado um caráter fascista e fazem uso da liberdade para justificar o individualismo radical e o ódio como ideologia (CATTANI, 2022 6 ;DÓRIA, 2020;CARVALHO;PAIVA, 2022;GOLPE..., 2021). Em contrapartida, buscamos averiguar a concepção de liberdade em Freire, que aponta para uma prática de liberdade como um agir comunitário e voltado para a cooperação que permite um crescimento conjunto tanto pessoal quanto social.…”
Section: Introductionunclassified